PRINCIPLES OF LEARNING AND MOTIVATION MATH BY NON-MATH MAJOR LEARNERS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article we discussed three research-based principles about guide effective math’s teaching and learning; also providing a high-quality mathematics education for all students, cognitive tasks as judging effects of mathematical operations, understanding mathematical properties, and making connections among math concepts.